Three essays on entrepreneurship and innovation: the role of late adopers - Jahanmir, Sara (2016)
This dissertation presents novel topics in entrepreneurship and innovation. In today’ markets, companies, especially those competing in red oceans, should look for new opportunities to remain competitive. To explore such opportunities, they need to come up with breakthrough ideas, which provide them with new market spaces and allow them to surpass competitors. One way of creating blue oceans is to explore what the competitors are ignoring. One rich source of novel ideas, which has been ignored by both researchers and practitioners, is late adopters. Late adopters are the last group of users who adopt a new product, service or technology. In this thesis, we explore this category of users and examine their potential as a source of innovative ideas and entrepreneurial opportunities. Chapter 1 of this thesis provides a brief introduction to the topics of entrepreneurship and diffusion of innovation. In chapter 2, we conduct an exploratory study in the entrepreneurial eco system of Cambridge. We aim at understanding the choices entrepreneurs make while making decisions, such as listening to early vs late adopters. In the third chapter, we present a measurement scale to access characteristics of late adopters, which facilitates the process of identifying them. Once we identify them, we need a customized new product development method to involve this category of users in idea generation. In chapter 4, we present the Lag-User Method. Through this method, we can benefit from the insights of late adopters. Among others, our studies reveal that late adopters can be among any demographic or social group. Their needs are different from those of other user categories. We find that unlike lead-user, late adopters do not create prototypes and need coaching to come up with incremental, really new or radical innovations. Insights from late adopters and laggards can help firms explore weaknesses of their products/services and target common needs across different markets, (e.g. the need for sophisticated technology that is simple to use). This will enable firms to cut costs and benefit from economies of scale while satisfying local needs and thereby increase their performance.